First record of the spider family Symphytognathidae in Europe and description of Anapistula ataecina sp. n. (Araneae) - Cardoso, Pedro; Scharff, Nikolaj (Zootaxa, 2009)
The spider family Symphytognathidae has never been recorded from Europe, being mostly present in tropical regions. Different collecting trips to a cave system in Portugal revealed several specimens of a new species of Symphytognathidae here described, Anapistula ataecina sp. n. This is one of the smallest spiders described to date. The species is almost exclusively known from the Frade Cave System in Portugal which is partly endangered by limestone quarries. No males were found to date despite many collecting trips to the caves during more than three years. Parthenogenesis could therefore be responsible for the species reproduction. Its web, with a sheet-like structure, seems atypical for the family and for the genus. Details on the eggsacs and spinneret morphology are also given.